Effects of genetic variability on rifampicin and isoniazid pharmacokinetics in South African patients with recurrent tuberculosis. (15th February 2019) - Naidoo, Anushka; Chirehwa, Maxwell; Ramsuran, Veron; McIlleron, Helen; Naidoo, Kogieleum; Yende-Zuma, Nonhlanhla; Singh, Ravesh; Ncgapu, Sinaye; Adamson, John; Govender, Katya; Denti, Paolo; Padayatchi, Nesri
Aim: We report the prevalence and effect of genetic variability on pharmacokinetic parameters of isoniazid and rifampicin.Materials & methods: Genotypes for SLCO1B1, NAT2, PXR, ABCB1  and UGT1A genes were determined using a TaqMan ® Genotyping OpenArray™. Nonlinear mixed-effects models were used to describe drug pharmacokinetics.Results: Among 172 patients, 18, 43 and 34% were classified as rapid, intermediate and slow NAT2 acetylators, respectively. Of the 58 patients contributing drug concentrations, rapid and intermediate acetylators had 2.3- and 1.6-times faster isoniazid clearance than slow acetylators. No association was observed between rifampicin pharmacokinetics and SLCO1B1, ABCB1, UGT1A  or PXR genotypes.Conclusion: Clinical relevance of the effects of genetic variation on isoniazid concentrations and low first-line tuberculosis drug exposures observed require further investigation.